English Learning Experiences of Generation Z High School Students in Indonesia: A Narrative Inquiry - Nazar Hasby; Natalina Asi; Indra Perdana; Lailatul Kodriyah; Neneng Islamiah; Fitra Ramadani; Alna Triskaya Angrum; Lailatun Najmiah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
This research explored the English learning experiences of Generation Z students in Indonesia using a narrative inquiry approach. Amidst the rapid advancement of digital technology, it was important to understand how Generation Z, born in the digital era, interacted with English language learning. This research aimed to explore students' perceptions, challenges, and lived experiences in learning English to contribute to developing more relevant teaching practices. A qualitative research design was applied by collecting personal narratives from five purposively selected students. Data were collected through semi-structured interviews and reflective writing tasks, then thematically analyzed to identify patterns and individual perspectives. The findings of this research identified four main themes: (1) a preference for informal digital platforms, such as social media and learning apps; (2) emotional changes related to self-confidence and peer comparison; (3) the role of teacher support and classroom environment in enhancing motivation; and (4) a growing view of English as a practical skill that was more important than mere academic achievement. The findings illustrated the dynamic relationship between personal motivation, socio-cultural influences, and technological engagement in shaping students' language learning journeys. The research concluded that recognizing and integrating students' narratives in teaching practices could increase learner engagement, encourage independence, and support more adaptive and empathic teaching strategies. These findings' implications were highly relevant for educators, curriculum developers, and policymakers to align English language teaching with the values and realities of Generation Z students.